SYSTEMATIC LITERATURE REVIEW OF RISK FACTORS AFFECTING TAKAFUL PRICING: A PRISMA-BASED APPROACH - Syakir, Asrulsani Muhammad; Zaki, Awang Chek Mohd; Liana, Ismail Isma (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Takaful, or Islamic insurance, is an alternative to conventional insurance and an integral part of Islamic finance. It is founded on the principles of mutual risk-sharing and cooperative contribution. Takaful pricing plays a critical role in ensuring sustainability, fairness, and Shariah compliance within Islamic insurance systems. Takaful differs from conventional insurance in several key components, including pricing. Pricing within Takaful and conventional insurance differs, posing a complex, strategically significant challenge for operators regarding the risk factors that affect pricing. Nonetheless, this study aims to identify and synthesise the key risk factors affecting Takaful pricing through a systematic literature review approach. A systematic literature review was conducted based on the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) statement 2020. This approach was conducted by the researcher across various databases, including Scopus, Web of Science, ScienceDirect, and Google Scholar. In this study, a systematic literature review was conducted based on the articles published from 2000 to 2025. A total of 562 articles were found, and 51 articles were selected based on the inclusion criteria. As a result of this approach, four major determinants identified as risk factors affecting Takaful pricing were found that are demographic, financial, operational, and macroeconomic. Demographic factors, such as age, gender, marital status, education, and income, that affect mortality will influence the pricing. Financial factors such as investment returns, solvency ratio, and adequacy play a critical role in pricing sustainability. Operational factors, such as claims ratio, expense ratio, underwriting, and digitalisation, play a critical role in pricing margin. Macroeconomic factors, such as inflation, GDP, unemployment rate, and exchange rate, play an indirect role in pricing. The study proposes an integrated conceptual framework to guide actuaries, regulators, and Takaful operators in developing sustainable pricing strategies.